2006
DOI: 10.1152/ajplung.00042.2005
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin agonist with thromboxane synthase inhibitory activity (ONO-1301) attenuates bleomycin-induced pulmonary fibrosis in mice

Abstract: . Prostacyclin agonist with thromboxane synthase inhibitory activity (ONO-1301) attenuates bleomycin-induced pulmonary fibrosis in mice. Am J Physiol Lung Cell Mol Physiol 290: L59 -L65, 2006. First published September 9, 2005 doi:10.1152/ajplung.00042.2005The balance between prostacyclin and thromboxane A2 (TXA2) plays an important role in pulmonary homeostasis. However, little information is available regarding the therapeutic potency of these prostanoids for pulmonary fibrosis. We have recently developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 34 publications
4
53
0
Order By: Relevance
“…The pathological features of IPF are fibroblast proliferation, increased amounts of extracellular matrix and varying degrees of persistent inflammation of the alveolar septa [2]. Recent reports have suggested that leukotrienes (LTs), which are arachidonic acid metabolites, are important regulators of pulmonary fibrosis [3,4].…”
mentioning
confidence: 99%
“…The pathological features of IPF are fibroblast proliferation, increased amounts of extracellular matrix and varying degrees of persistent inflammation of the alveolar septa [2]. Recent reports have suggested that leukotrienes (LTs), which are arachidonic acid metabolites, are important regulators of pulmonary fibrosis [3,4].…”
mentioning
confidence: 99%
“…The regimen used in the experiments was determined from those used in previous papers. [8][9][10][11][12] Animals and cardiac transplantation: Male inbred mice (4 to 6 weeks, 20-25 g) were used. The male BALB/c (H-2 d ) and C57BL/6 (H-2 b ) mice (4-6 weeks, 20-25 g) were obtained from Japan Clea, Co (Tokyo), and this combination was used as the major histocompatibility complex total allomismatch group for analysis of acute rejection.…”
Section: Methodsmentioning
confidence: 99%
“…6) Because ONO-1301MS does not have prostanoid structures, it is not easily metabolized and its effects remain for a longer time compared with other prostacyclin analogs, such as beraprost or iloprost. [7][8][9][10] It has been reported that local administration of a slow releasing form of ONO-1301MS into ischemic murine hearts was effective at preventing left ventricular remodeling and improving the survival rate.…”
mentioning
confidence: 99%
“…We have already reported that ONO-1301 showed a beneficial effect by inhibiting the MEK/ERK pathway, 11 and we also reported that repeated administration of ONO-1301 attenuated the development of bleomycin-induced pulmonary fibrosis and improved survival of the affected mice, at least in part by inhibiting TXA2 synthesis and activating the cAMP/PKA pathway. 22 Binding of ONO-1301 to the IP receptor stimulates adenylate cyclase activity, which increases the level of cAMP, which then induces endogenous HGF production and increases PKA activity. 23 PKA has been shown to induce endogenous HGF production 23 and inhibit the MEK/ERK pathway.…”
Section: Inhibitory Effect Of Ono-1301 On Thromboxane Synthesismentioning
confidence: 99%